Faktor-Faktor Yang Mempengaruhi Mutu Pelaksanaan Proyek Peningkatan Jalan Tedubara-Pising Kabupaten Bombana - Ali, Rahmat; Lakawa, Irwan; Hawa, Sitti; Sufrianto, Sufrianto (Sultra Civil Engineering Journal (SCiEJ), 2022)
This study aims to analyze the factors that influence the quality of the implementation of improving the Tedubara-Pising street in Bombana Regency. This study uses quantitative data analysis techniques with a sample size of 30 respondents. The results showed that the factors affecting the quality of the Tedubara Pising road improvement in Bombana Regency were financial indicators (X3) 21.97%, followed by Human Resources indicators (X1) 20.14%, location indicators (X5) 19.68 %, material indicator (X2) 19.22%, and the lowest is equipment indicator (X4) 18.99%. Factors related to the quality of road improvement, namely the human resources variable with a value of 0.855 and material with a value of 0.853. This shows a very strong relationship